Komplikasi metabolik dan endokrin jangka panjang pada wanita setelah kehamilan dengan Diabetes Gestasional - Rika Wulandari; Yusri Dwi Lestari (Rena Cipta Mandiri, 2025)
Gestational diabetes (GDM) is a condition of increased blood glucose levels that is first detected during pregnancy, and not only affects the mother during pregnancy, but also increases the risk of long-term metabolic and endocrine complications after delivery. Women with a history of GDM are at higher risk of developing type 2 diabetes, dyslipidemia, thyroid disorders, and polycystic ovary syndrome (PCOS). These metabolic complications can appear within 5 to 20 years after pregnancy, with insulin resistance as the main triggering factor. In addition, thyroid disorders and PCOS can interfere with hormone function, which has an impact on the body's metabolic balance and reproductive health. Some risk factors that contribute to these long-term complications are obesity, family history of diabetes, age, and post-pregnancy lifestyle. Proper handling through routine screening, healthier lifestyle changes, and medical therapy are needed to reduce the risk of complications and improve the quality of life of women after pregnancy. With early detection and effective prevention, long-term complications due to GDM can be minimized, which can ultimately prevent women from the risk of other chronic diseases.